LEADERSHIPS EMOTIONAL INTELLIGENCE AND ITS DOWNSTREAM EFFECTS ON ENGAGEMENT AND TALENT RETENTION IN NAGPURS IT SECTOR - Kale, Snehal; Rahate, Vaishali (International Journal of Research -GRANTHAALAYAH, 2025)
This study investigates how leadership emotional intelligence affects talent retention and employee engagement in Nagpur's IT industry. The relevance of emotional intelligence (EI) in influencing motivation, long-term commitment, and relationships at work is expanding as it is seen as a critical leadership quality. In order to determine how emotionally intelligent behaviorslike empathy, self-awareness, and effective communicationexhibited by leaders affect employees' experiences and decisions to stay with a company, the study uses a descriptive research design and questionnaire-based data collection from 150 employees across IT companies in Nagpur. According to the results, most workers believe that emotionally savvy leadership plays a big role in keeping them engaged and on board. Nonetheless, disparities in leadership approaches point to the necessity of more comprehensive and methodical programs for developing emotional intelligence. The study comes to the conclusion that, in a competitive talent market, investing in Emotional Intelligence (EI) training may improve workplace culture, increase employee happiness, and fortify organisational stability.